Heavy metals in the sediment of Sava River, Slovenia - Kotnik, Jože; Horvat, Milena; Milačič, Radmila; Ščančar, Janez; Fajon, Vesna; Križanovski, Andrej (Geologija, 2003)
The Sava River is the longest river in Slovenia and it has been a subject of heavy pollution in the past (Štern & Förstner 1976). In order to determine the anthropogenic contribution of selected metals (Cd, Co, Cr, Cu, Fe, Hg, Ni, Pb and Zn) to background levels, concentrations of these metals were measured in sediments at several downstream locations. An extracting procedure using 25% (v/v) acetic acid was applied for estimation of the extent of contamination with heavy metals originating from anthropogenic activities. In addition, a normalization technique was used to determine background, naturally enriched and contamination levels. Aluminum was found to be good normalizer for most of the measured elements. The results suggest that an anthropogenic contamination of certain metal is not necessarily connected to easily extractable fraction in 25% acetic acid. As a consequence of anthropogenic activities the elevated levels of all measured elements were found near Acroni Jesenice steelworks and at some locations downflow from biggest cities.